Sentinel dosing: A proposed algorithm to guide decision making on which cohorts in early phase clinical pharmacology trials should use this approach - Heuberger, Jules A. A. C.; Jongh, Perry; Hoogdalem, Ewoud‐Jan; Tamminga, Wim; Graeff, Pieter; Groeneveld, Geert Jan (British journal of clinical pharmacology, 2025)
Aim The aim of this paper is to describe a proposal for an algorithm to guide decision making on which cohorts in early phase pharmacology trials should employ a sentinel approach, thereby standardising and harmonising practices, and improving decision making around sentinel dosing. Sentinel dosing is an approach described in EMA guidelines; however, the guidance does not provide detail on which cohorts or dose levels sentinel dosing applies. Methods This algorithm was designed using the expertise of senior scientific staff from the largest clinical research organisations in the Netherlands and after consultation with members of the ethics committee handling most early phase clinical drug trials in the Netherlands. Results The algorithm describes a decision tree considering different aspects of the design of the trial, the IMP, and the prior knowledge of the IMP based on (pre)clinical data, to be used by investigators and regulators. Hereby the decision‐making process on sentinel cohorts will be tailored to the specific IMP and information available. Starting in 2024, all three expert Phase 1 units that co‐authored this paper are using the algorithm as guidance for decision‐making on the implementation of sentinels in trials that are submitted to the EC Stichting BEBO. Conclusion The algorithm provides further guidance and specification on when to implement sentinel dosing in early phase clinical trials, thereby creating a standardised and harmonised approach, which will improve the protection of subject safety and trial efficiency.